Risk forecasting of the femoral head dislocation and its prophylaxis at total hip joint replacement - Filipenko, Volodymyr; Kolesnichenko, Vera; Mezentsev, Volodymyr; Ovchynnikov, Oleh (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
One of the most frequent complications after total hip replacement is femoral head dislocation. Risk of its forecasting is topical in orthopeadic field. Objective: on the base of retrospective and prospective analysis we wanted to define the quantitative criteria of risk forecasting and to work out the method of dislocation prophylaxis after total hip replacement. Methods: retrospective analysis of clinical and roentgenological examination of 80 patients after total hip replacement was conducted. Neutral cup liner was used. Quantitative criteria of risk forecasting were made with consistent forecast procedure. Prospective study of replacement results was made. We used author’s method — liner with visor — 24 patients (11 men, 13 women, average age (55.0 ± 18.4) years old). Results: the risk factors of the femoral head dislocation are: overweight (82,5 %), muscles weakness in the region of the hip joint (67,5 %), age older than 61 years old (52,5 %), non-compliance of orthopaedic mode in the postoperative period (50,0 %). Computational table was worked out in order to forecast the risk of the femoral head dislocation. We suggest the method of prophylaxis and the treatment with certain position of implant components and the usage of liner with visor. Conclusions: on the base of retrospective analysis of clinical and roentgenological assessment we could reveal the risk factors of femoral head instability after THR. The most significant forecast signs were oversized movements in the hip joint (I = 1.44), femoral head diameter less than 32 mm (I = 0 .50), age older than 61 years old ( I = 0 .47). Favorable result of the surgery was due to 10° cup liner.